Faith, Death, and the Internet in Norway and Sweden - Gustavsson, Anders (Traditiones, 2022)
The all-inclusive issue in studies of memorial websites on the internet concerns how mourners express their emotions and concepts of belief regarding a deceased person’s afterlife. The living believe that their ultimate contact with the deceased will occur after their own death. In Sweden, this also applies to deceased pets. Memorial websites to the deceased generally contain far more traditional Christian concepts in Norway than in Sweden. In Sweden one observes more of a diffuse, general religiosity that can remind one of New Age modes of thought in which individualism.